Policy on Credit Hour Definition (2021)
A system-wide memorandum dated December 21, 2020, outlines the system's definition of a credit hour, and directs all CSU campuses to "develop, communicate and implement procedures for regular, periodic review of this credit hour policy to ensure that credit hour assignments are accurate, reliable and consistently applied, " by June 2021. It indicates that, "campuses will be responsible (effective summer 2021) for publishing a clearly stated practice or process that ensures they are in compliance with the student credit hour definition."The CSU definition of a credit hour that applies at the writing of this policy is thus: 1. A credit hour approximates not less than: a. One hour of direct faculty instruction and a minimum of two hours of out-of-class student work each week for approximately 15 weeks for one semester or trimester hour of credit (or 10 to 12 weeks for one quarter hour of credit) or the equivalent amount of work over a different amount of time; or b. At least an equivalent amount of work as required in paragraph 1. a. of this definition for other academic activities as established by the institution including laboratory work,internships, practice, studio work and other academic work leading to the award of credit hours; and 2. Permits an institution, in determining the amount of work associated with a credit hour, to take into account a variety of delivery methods, measurements of student work, academic calendars, disciplines and degree levels. Institutions have the flexibility to award a greater number of credits for courses thatrequire more student work. In light of these definitions, the following is a policy on regular and periodic review to ensure the accuracy, reliability, and consistency of credit hour applications.